Colorectal cancer vaccines: The current scenario and future prospects - Jia, Wenqing; Zhang, Tao; Huang, Haiyan; Feng, Haoran; Wang, Shaodong; Guo, Zichao; Luo, Zhiping; Ji, Xiaopin; Cheng, Xi; Zhao, Ren (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is one of the most common cancers worldwide. Current therapies such as surgery, chemotherapy, and radiotherapy encounter obstacles in preventing metastasis of CRC even when applied in combination. Immune checkpoint inhibitors depict limited effects due to the limited cases of CRC patients with high microsatellite instability (MSI-H). Cancer vaccines are designed to trigger the elevation of tumor-infiltrated lymphocytes, resulting in the intense response of the immune system to tumor antigens. This review briefly summarizes different categories of CRC vaccines, demonstrates the current outcomes of relevant clinical trials, and provides particular focus on recent advances on nanovaccines and neoantigen vaccines, representing the trend and emphasis of CRC vaccine development.